2014
DOI: 10.3109/19401736.2014.913151
|View full text |Cite
|
Sign up to set email alerts
|

The complete mitochondrial genome of the subspecies, Phrynocephalus erythrurus parva (Reptilia, Squamata, Agamidae), a toad-headed lizard dwell at highest elevations of any reptile in the world

Abstract: The complete mitochondrial genome was sequenced from the toad-headed viviparous lizard subspecies, Phrynocephalus erythrurus parva, which occupies the highest regions of any reptile on the earth. The mitogenome sequence was 16,431 bp in size, with the overall base composition of H-strand is T: 26.06%, C: 25.14%, A: 36.45%, G: 12.35%. It consists of 13 protein coding, 22 tRNA, 2 rRNA genes and 3 control regions, and its gene order and gene content were identical with the published congeneric mitogenomes of othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
2
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
2
2
0
1
Order By: Relevance
“…Nucleotide composition analysis indicated that the three mitogenomes displayed a significant bias toward adenine (A)/thymine (T), with overall A + T content of 62.3% in P. helioscopus varius I, 62.4% in P. helioscopus varius II, and 62.3% in P. helioscopus cameranoi ( Table S4 ). This base pattern is congruent with most previously reported mitogenomes in Phrynocephalus [ 55 , 56 , 57 , 58 , 59 ]. The PCGs, rRNAs, and tRNAs were also A/T-biased in nucleotide composition.…”
Section: Resultssupporting
confidence: 92%
“…Nucleotide composition analysis indicated that the three mitogenomes displayed a significant bias toward adenine (A)/thymine (T), with overall A + T content of 62.3% in P. helioscopus varius I, 62.4% in P. helioscopus varius II, and 62.3% in P. helioscopus cameranoi ( Table S4 ). This base pattern is congruent with most previously reported mitogenomes in Phrynocephalus [ 55 , 56 , 57 , 58 , 59 ]. The PCGs, rRNAs, and tRNAs were also A/T-biased in nucleotide composition.…”
Section: Resultssupporting
confidence: 92%
“…The subgenus Megalochilus was originally established for the largest species of Phrynocephalus-the psammophilous secret toadheaded agama, P. mystaceus [127]. Our analyses agree with the earlier data of Solovyeva et al [2,21] in recognizing two deeply divergent reciprocally monophyletic lineages within Megalochilus with non-overlapping distributions (Figure 2C): P. mystaceus inhabiting Middle Asia, southern Russia, Kazakhstan and western Xinjiang of China, and the recently described P. m. khorasanus from deserts of northeastern Iran [26]. The divergence between these lineages in COI gene is significant (p = 7.2%, see Supplementary Table S2), it was dated as 2.1 mya [2].…”
Section: Megalochilus (Phrynocephalus Mystaceus Species Group)supporting
confidence: 89%
“…A number of recent studies have focused on molecular taxonomy and phylogenetic relationships of various Phrynocephalus species or species complexes [7,8,[13][14][15][16][17][18][19][20][21] and on structure of complete mitochondrial genomes [22][23][24][25][26]. However, there is a lack of comparative phylogenetic works based on large datasets for the whole genus, thus, further studies are needed to access the genetic diversity across the genus Phrynocephalus, estimate the levels of cryptic diversity, and eventually to stabilize the taxonomy of the group.…”
Section: Introductionmentioning
confidence: 99%
“…青藏高原 作为全球面积最大且平均海拔最高的地区, 相比其他 高地, 长期受到生物学家的关注. 目前世界上海拔分 布最高的两栖动物如高山倭蛙(Nanorana parkeri, 最 高海拔约5100 m)等(http://www.Amphibiachina.Org) [17] 和爬行动物如红尾沙蜥(Phrynocephalus erythrurus, 最 高分布海拔5300 m左右)等 [18] 均分布于此.…”
unclassified